The deficiency of language in perspective the martyr Muhammad Al-Sadr in the book of Menna Al-Mannan in Defense of the Qur’an. - Rahim Maaleh, Salem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This research sheds light on the effort of the martyr Muhammad al-Sadr in explaining the deficiency of language in the writing of Minna al-Mannan in defense of the Qur’an because of the great importance of language in communication, conveying meaning in the forms of words, and bringing out what is in the soul into the space of hearing, and thus it expands for many words. The language suffers from a deficiency in this, especially in the Holy Qur’an. Thus, I examined the causes of the language’s deficiency and its manifestations, such as repetition, metaphor, and interpretation, to arrive at the deficiency of the language in the Holy Qur’an according to the foundation of the martyr Muhammad al-Sadr, and proven by evidence for that